Distributed leadership and the shaping of infrastructure project portfolios - Daniel Woodier; Christian Thuesen (Project Leadership and Society)
Important socio-technical changes are increasingly being implemented through major programmes or portfolios of projects (Maylor et al., 2006). These interventions, while necessary for modernisation and the green transition, cause short-term disruption which generates discord and opposition impacting stakeholder perception. The long-term sustainable transformation of rail transportation infrastructure toward electrification, greater speed, digital signalling, creates great benefit in terms of energy and carbon efficiency, reliability, and punctuality, but the short-term disruption caused by the projects can reduce the attractiveness of this mode of transport. This paper reports findings from an embedded case study with the Danish national railway infrastructure owner and analyses how the leadership team uses distributed leadership as a dynamic process of project and portfolio shaping which internalises diverse external perspectives and reconciles competing objectives. Using the “Tesseract” four-dimensional model of project success Ika and Pinto (2022a)to frame these competing interests, this paper presents a model of how distributed leadership shapes the railway project portfolio through the considerations of coherence, disruption, and benefit.